Effective Practices of Updating the Subjectivity of the Mother during the Restoration of Parental Rights - Vasyagina, N.N.; Mazurchuk, E.O. (Bulletin of Practical Psychology of Education, 2020)
Taking into account the special importance of the blood family for the psychological well-being of the child, the problem of preparing women who restore parental rights to the implementation of educational functions is of particular relevance. One of the most important conditions for the effectiveness of a family education is the integrative characteristic of mother’s personality — her subjectivity, which reflects an active-selective, proactive and responsible attitude to educational activities, a child and her to herself as a subject of a family education. The article describes the effective practices that make up the core of the program of psychological and pedagogical support “I am a subject of education”. The program is a phased organization of activities and events that launch psychological mechanisms of reflected subjectivity and reflection. During the implementation of the program, conditions are created that allow mothers to realize and accept responsibility for the process and result of upbringing, the mothers activate semantic foundations of educational activity, ensure the design of a positive “I am a mother” image of herself, harmonize the attitude towards the child and to herself as a subject of family education. Учитывая особую значимость кровной семьи для психологического благополучия ребенка, особую актуальность приобретает проблема подготовки женщин, восстанавливающих родительские права, к реализации воспитательных функций. Одним из важнейших условий эффективности семейного воспитания выступает интегративная характеристика личности матери — субъектность матери, отражающая активно-избирательное, инициативно-ответственное отношение к воспитательной деятельности, ребенку и к самой себе как субъекту семейного воспитания. В статье описаны эффективные практики, составляющие ядро программы психолого-педагогического сопровождения «Я — субъект воспитания». Программа представляет собой поэтапную организацию мероприятий и событий, запускающих психологические механизмы отраженной субъектности и рефлексии. В ходе реализации программы создаются условия, позволяющие матерям осознать и принять ответственность за процесс и результат воcпитания, у матерей активизируются смысловые основания воспитательной деятельности, обеспечивается проектирование позитивного образа «Я-мать», гармонизируется отношение к ребенку и к самой себе как субъекту семейного воспитания.